The effect of learning Think Talk Write model with Powerpoint assistance on students' mathematics learning outcomes - Abdul Muis; Endra Priawasana (SAINTIS Publishing, 2022)
This study aims to know the effect of the Powerpoint-assisted Think Talk Write (TTW) learning model on student learning outcomes. The type of study is experimental and the design is one group pretest-posttest design. This type begins with measuring the initial ability of students than giving treatment and then giving a remeasurement or posttest. This analysis was conducted to determine the effect of the Powerpoint-assisted TTW learning model on students learning outcomes. The results of the study showed that the significance value between the pretest and posttest was 0.002 and the sign value was 0.05. Based on the decision that the sign value is 0.002 and less than 0.05 which means that there is a significant difference between the pretest and posttest there is a significant effect on the treatment given. This means that there is a significant influence on the Powerpoint-assisted TTW learning model on student learning outcomes.